LEVERAGING KNOWLEDGE DIVERSITY IN HIERARCHICALLY DIFFERENTIATED TEAMS: THE CRITICAL ROLE OF HIERARCHY STABILITY - Gray, Steven M.; Bunderson, J. Stuart; van der Vegt, Gerben S.; Rink, Floor; Gedik, Yeliz (Acad Management, 2023)
Past research has been equivocal about the information sharing and performance effects of knowledge diversity in teams. In an attempt to resolve this equivocality, scholars have suggested that status hierarchy may play a role, proposing that status differences can constrict team-level information sharing in diverse teams by privileging the knowledge of higher-status members and discounting the knowledge of lower-status members. Although there is some evidence to support this notion, there is also evidence to suggest that status differences may amplify information sharing in diverse teams by offering status enhancement incentives to members who share unique knowledge. In this paper, we reconcile these different predictions by suggesting that the effects of status hierarchy on the relationship between knowledge diversity and team information sharing will depend on the stability of the hierarchy. Using a diverse sample of 156 teams across 110 organizations, we found that status differences constricted information sharing in knowledgediverse teams when hierarchy stability was high and amplified information sharing in knowledge-diverse teams when hierarchy stability was low. These information sharing effects, in turn, affected team performance. Our study highlights how hierarchy stability is critical for understanding whether status differences constrict or amplify information sharing in knowledge-diverse teams.
Keywords: Decision-Making Groups; Top Management Teams; Unshared Information; Shared Information; Diagnosing Groups; Social Hierarchy; Work Groups; Power; Performance; Leadership